Ownership Structure and Financial Distress: Investigating the Moderating Effect of Audit Quality - Sarker, Niluthpaul; Hossain, S. M. Khaled (International Journal of Economics and Financial Issues, 2023)
The study examines the effect of ownership structure and the moderating role of audit quality on the likelihood of firms’ financial distress. 144 DSE-listed manufacturing companies were chosen to design the sampling frame for performing the research. Ten manufacturing industry categories were selected, and data from 1310 firm-year observations were collected during the research period 2012-2021 from several sources, including annual reports of the companies, the World Bank Database etc. Using the Two-stage-least-square (2SLS) model estimation technique, the study disclosed that managerial ownership, foreign ownership, ownership concentration, and government ownership have a significant negative influence on the likelihood of firms’ financial distress, whereas institutional ownership and public ownership are positively correlated with the financial distress. It is also evidenced that firms’ shareholders’ influence and GDP growth rate have a noteworthy negative influence on distress possibilities. In contrast, firm size is positively correlated with the financial distress of the firms. No significant effect of firm age and inflation rate on financial distress was identified. The study period covered only 12 years, from 2012-2021, and focused on the manufacturing industries of Bangladesh. The study offers robust evidence on the role of ownership structure on the stability of manufacturing companies using a multidimensional approach of ownership structure and moderating effect of audit quality, which has financial, legal, and social implications in the context of emerging economies like Bangladesh.